О фильтрации магнитных объектов по глубине посредством аналитического продолжения в поле эквивалентных источников - Черная, О.А.; Дубовенко, Ю.И. (Геоінформатика, 2015)
В статье рассматривается методика для интерпретации и уточнения положения археологических объектов с помощью метода фильтрации в эквивалентном слое. Задача состоит в том, чтобы выделить все необходимые аномалии, включая аномалии малой амплитуды, в чистом виде и представить их в наглядной форме. С этой целью произведены исключение регионального фона и фильтрация помех. Использовано аналитическое продолжение вверх как способ разделения источников на различных глубинах. Предложен алгоритм восстановления потенциального поля по распределению эквивалентных источников: исключение регионального фона; нахождение разностного поля остаточных аномалий; вычисление намагниченности от слоя эквивалентных источников; фильтрация аномалий. Сделано допущение, что данные грави- и магнитного поля не содержат явно информации о глубине источников и что наблюденное магнитное поле является суммой регионального поля, остаточного поля и обобщённого шума. Использован набор взаимно не коррелируемых распределений тонкослоистых источников на разных глубинах для моделирования поля. На основе анализа магнитных данных осуществлён пересчёт вверх магнитных аномалий с целью их археологического истолкования. В результате аналитического продолжения аномалии разделены по глубинности источников. По рассчитанному полю от источников в эквивалентном слое определены контуры аномалий. Дополнительный расчёт горизонтального градиента магнитной индукции дал возможность уточнить классификацию локальных аномалий по амплитуде. Результаты интерпретации имеют качественный характер, но их использование дало возможность локализовать места раскопов. У статті розглянуто методику для інтерпретації і уточнення положення археологічних об’єктів за допомогою методу фільтрації в еквівалентному шарі. Завдання полягає в тому, щоби виділити усі необхідні аномалії, включаючи аномалії малої амплітуди, в чистому вигляді і представити їх у наочній формі. З цією метою зроблено виключення регіонального фону і фільтрацію перешкод. Використано аналітичне продовження вгору як спосіб розділення джерел на різних глибинах. Запропоновано алгоритм відновлення потенціального поля за розподілом еквівалентних джерел: виключення регіонального фону; знаходження різницевого поля залишкових аномалій; обчислення намагніченості від шару еквівалентних джерел; фільтрація аномалій. Зроблено припущення, що дані граві- і магнітного поля не містять явно інформації про глибину джерел і що спостережене магнітне поле є сумою регіонального поля, залишкового поля і узагальненого шуму. Використано набір взаємно не корельованих розподілів тонкошарових джерел на різних глибинах для моделювання поля. На підставі аналізу магнітних даних здійснено перерахунок угору магнітних аномалій з метою їх археологічного тлумачення. В результаті аналітичного продовження аномалії розділено за глибинами джерел. Розрахунок поля від джерел в еквівалентному шарі дав змогу визначити контури аномалій. За додатковим розрахунком горизонтального градієнта магнітної індукції уточнено класифікацію локальних аномалій за амплітудою. Результати інтерпретації мають якісний характер, але за ними можна локалізувати місця розкопів. Purpose. The paper considers the techniques and methods aimed at interpretating and specifying the location of the archaeological sites using the equivalent layer filtering approach. The task is to outline all the required anomalies (including small) per se and present them in a visual form. For this purpose, it is necessary to perform two procedures: remove the regional background and to filter noise.
Design/methodology/approach. We studied the possibility of using filtration by means of analytical continuation in the top half-space as a way of separating sources at various depths. We offer the following algorithm of restoring potential field by the equivalent distribution of sources: Elimination of the regional field, Estimation of the residual field anomalies, Calculation of the magnetization, Filtering the anomalies. There are a number of assumptions made, and one must keep in mind that magnetic and gravity data contain no inherent information about the depth of source and the observed magnetic field to be the sum of the regional field, the residual field, and aggregate noise. We also used assemblages of mutually uncorrelated thin source distributions at various depths to model the field as equivalent source layers.
Findings. Based on the analysis of the magnetic data survey acquired for a Pineview park of 30x80 m, we calculated upwards magnetic anomalies in order to perform their archaeological interpretation. An analytical continuation procedure allows us to divide the anomalies by the sources depths. Field calculation from the sources in an equivalent layer by means of calculating of the residual field from the anomalous sources boundaries allowed us to define the contours of the magnetic anomalies. Additional calculation of the horizontal gradient of magnetic induction allowed us to adjust the classification of local anomalies by the amplitude.
Practical value/implications. The conducted research proves the necessity to create a general database on processing archaeological objects of geological heritage (geosites) of Ukraine under a single state program. The research was also successful in testing a method for analytical extension of components of a magnetic field into the field of equivalent sources within the sample data for Pineview park (30x80 m) to do their archaeological interpretation. Additional information used for the qualitative analysis is the calculation of the horizontal gradient of the magnetic induction in order to specify the classification of the local anomalies by the amplitude. The transformations above one can be complemented with other filters. The results of the interpretation are of qualitative character, nevertheless they us allowed us to localize the location of excavations.